Nagi, Akif - (:unkn) unknown (My University, 2026)
Akif Nagi was born on August 13, 1957, in the village of Papravend, Agdam district. In 1979, he enrolled in the Faculty of History at Azerbaijan State University (now BDU), and in 1982, he entered Moscow State University to continue his education. He graduated with honors in 1985 and began working at the Department of History at the Azerbaijan Polytechnic Institute (now Technical University) that same year. He defended his dissertation in 1991, earning a Ph.D. in History. In 1993, he became an associate professor at the same university. He is a politician. He served as the chairman of the Karabakh Liberation Organization and later of the Free Homeland Party. He is the author of articles and textbooks. He is a specialist in history who has conducted numerous engaging lessons and works to improve the teaching of the subject and foster a love of history among young people. He currently serves as an associate professor at the Azerbaijan Technical University.
Keywords: History